Creation of wheat stable somaclonal lines with valuable traits on the base of biotechnology (Experimental biology, 2015)
The long-term plant regeneration technology developed by us can be use for obtain of somaclonal lines with stableinherited valuable traits. It was shown that some of these traits (dwarf, high grain mass, large grain, high grain yield)were fully maintained and increased in next generation of Otan and Celinnaya 3C cvs. somaclonal lines. The differencessomaclonal lines as compared to the original variety and between themselves were revealed by the use of PCR analysiswith IRAP-markers.
Keywords: somaclonal variants; plant regeneration; inheritance; DNA; PCR; IRAP-markers.